ANALISIS KINERJA KEUANGAN PADA PT BANK MUAMALAT INDONESIA, Tbk. - Tarisa Salsabella; M. Thoyib; Marsahanda Aprilia (EKSISTANSI, 2021)
Financial statement analysis is an essential tool to obtain information about the financial condition and performance of the company during the period. By analyzing the financial statements, it can be seen whether the financial performance is in a healthy or unhealthy condition. The cause of a bank is beneficial if the ratio is above the predetermined average and is said to be harmful if the ratio value is below the average. The object of this research is one of the banks in Indonesia, namely PT Bank Muamalat Indonesia Tbk. This study was conducted to predict financial performance using the Camel method. This bank is the first Islamic bank that was established in 1991. Based on the economic reports from the official website of PT Bank Muamalat Indonesia Tbk, profits fluctuate from year to year, and the amount of costs incurred is almost the same as the income received. This study aims to (1) determine the causes of the rise and fall of profits for three consecutive years; (2) to find out and analyze the impact of the number of costs incurred by PT Bank Muamalat Indonesia Tbk.